1997
DOI: 10.1097/00007632-199708150-00009
|View full text |Cite
|
Sign up to set email alerts
|

Acute Axis Fractures

Abstract: Type II odontoid fractures have the highest nonunion rate and were associated with dens displacement of 6 mm or greater. Early surgical fusion is recommended for acute fracture instability despite external immobilization, transverse ligament disruption, Type II odontoid fractures with dens displacement of at least 6 mm on admission, or severe Francis grade or Effendi-type hangman's fractures. Otherwise, nonoperative management is sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(102 citation statements)
references
References 45 publications
3
97
0
2
Order By: Relevance
“…In a current literature review [33], the incidence of malunion reported was low in type II and III odontoid fractures following halo treatment (5 and 10%, respectively). However, with the latter the articular facets of C2 are frequently affected and symptomatic malunion or segmental C1-2 deformation after nonsurgical treatment has been observed several times [5,10,13,14,20,24,26,29,33,35,36,42,55,57]. Clark [10] already stretched that type III odontoid fractures were 'not benign as previously reported'.…”
Section: Discussionmentioning
confidence: 86%
“…In a current literature review [33], the incidence of malunion reported was low in type II and III odontoid fractures following halo treatment (5 and 10%, respectively). However, with the latter the articular facets of C2 are frequently affected and symptomatic malunion or segmental C1-2 deformation after nonsurgical treatment has been observed several times [5,10,13,14,20,24,26,29,33,35,36,42,55,57]. Clark [10] already stretched that type III odontoid fractures were 'not benign as previously reported'.…”
Section: Discussionmentioning
confidence: 86%
“…Burke et al [1] analyzed 165 patients with acute injuries of the axis vertebra and noted that the injuries consisted of 68 (41 %) dens fractures, 62 (38 %) cases of hangman's fracture and various other fractures (21 %). Greene et al [2] also analyzed acute axis fractures in 340 patients, and reported that odontoid fractures were the most common, occurring in 199 of the patients (58 %), followed by hangman's fractures in 74 patients (22 %) and miscellaneous fractures in 67 patients (20 %), most of which involved the vertebral body or the lateral mass. The treatment of odontoid fractures, which account for a large percentage of axis fractures, has been reported previously by many authors; however, Denaro et al [3] noted that, although the available literature cannot be used to determine the best surgical approach for treating odontoid fractures, the overall bone union mortality and complication rates are in line with the current recommendations for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A meaningful number of subtypes of C2-fractures exists where complete reduction, normal C1-2 rotation and a physiological anatomy is difficult to restore [1,10,11,34,42,43,71,82]. Likewise, a non-anatomical posttreatment C2-alignment, resembling a malunion, can cause significant symptoms even indicating fusion C1-2 [13,26,30,42,47,51,52,67,70,71,78,79] as it had to be done in one of our cases (Fig. 3), two others being scheduled (Fig.…”
Section: Malunion Of C2mentioning
confidence: 88%
“…Several patients were noted to have combinations of reduced ROM, persistant pain, a malunion or AAOA. Müller [49] stressed the importance of anatomical alignment in C2-fractures and the findings of the current study give evidence that with an increasing number of C2-fragments, deformation of the C2 vertebral body and particularly fractures of the C2 lateral mass clinical outcome drops: Fractures involving the C2 articular pillar can be isolated articular or lateral mass fractures or extensions of vertebral body fractures [5,26] and were found to be prone to a high rate of nonanatomical union [21] frequently indicating secondary fusion of C1-2 [30,67,70]. Up to 50% of Hmfx involve the articular facets of C2 and in the largest sample regarding anterior fusion C2-3 for the treatment of unstable Hmfx, Koller [46] observed a decreased functional and clinical outcome with a subset of patients having reduced rotation C1-2 and motion induced C2-referred pain.…”
Section: Clinical Outcomementioning
confidence: 93%